KEKERASAN SIMBOLIK DIGITAL DEEPFAKE PORNOGRAFI ANALISIS SOSIOLOGIS DAN PELANGGARAN HAM DI LINGKUNGAN PENDIDIKAN TINGGI - Shintia, Mira; Selvita Andriani; Henni Martini; Jose Vargas Rodriguez; Rudy Kurniawan (STKIP Subang, 2026)
The development of Artificial Intelligence (AI) technology has created new forms of digital sexual violence, particularly deepfake pornography that manipulates individuals’ visual identities without consent. This phenomenon has become a serious issue as it not only violates privacy but also relates to human rights violations, the reproduction of digital patriarchy, and insecurity within academic spaces. This study aims to analyze deepfake pornography as a form of digital symbolic violence and human rights violation in higher education through a case study at Udayana University. This research employs a qualitative method with a critical case study approach. Data were collected through documentation studies and literature reviews derived from online media, legal regulations, academic journals, and relevant literature on digital sexual violence. The analysis applies Pierre Bourdieu’s critical sociology perspective and a digital human rights approach. The findings reveal that deepfake pornography represents a form of digital symbolic violence that reproduces patriarchal power relations through AI technology. Such practices violate victims’ rights to dignity, privacy, security, and justice. Furthermore, this study identifies the existence of “institutional digital insecurity” within higher education caused by weak digital ethics governance and inadequate protection for victims of technology-based sexual violence. The novelty of this research lies in the development of the Digital Power Relations Model in deepfake pornography by integrating symbolic violence theory, digital patriarchy, digital human rights, and AI technology within the context of academic spaces.